Nanocellulose-based Biomaterial Ink Hydrogel For Uptake/release Of Bovine Serum Albumin - Wan Nazihah Liyana Wan Jusoh; Denesh Mohan; Mohd Shaiful Sajab; Peer Mohamed Abdul; Hatika Kaco; Gongtao Din; Rubiyah Baini (MDPI, 2024)
Indexed by WOS/Scopus/ERA